THE DIAGNOSTICS OF SHAPING THE MANAGEMENT COMPETENCE OF THE FUTURE PRINCIPALS OF INSTITUTIONS OF COMPREHENSIVE EDUCATION - Darmanska, I.N (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
The problem of formation of managerial competence of the future managers of comprehensive educational institutions has been studied in the article. The present article gives a detailed analysis of the diagnostics of postgraduates regarding shaping the management competence. The diagnostic data were collected based on determination of a level of awareness of future specialists in terms of the use of key management notions, evaluation of necessity in shaping the management competence, personal managerial skills, shaping individual kinds of competence according to its compounds. The article presents a pedagogical experiment conducted to verify the effectiveness of the pedagogical system of forming the managerial competence of future managers of institutions of general secondary education on specialty 073 «Management» in the process of continuous professional training. The methodological basis of the pedagogical system is based on the concept of succession and continuity of the formation of managerial competence of future managers of institutions of general secondary education, laws, rules, approaches, general and special principles of management. The developed system was implemented through the introduction of elements of the structural-functional model, general and special organizational and pedagogical conditions, innovative technologies, practical methods and techniques. The research covered estimation of the level of formation of the theoretical and practical components of managerial competence of future managers of institutions of general secondary education to check the effectiveness of the created pedagogical system. On the basis of generalizing, positive and negative sides of the process of preparation of managerial personnel for the sphere of education have been determined. The predicted directions of improving the educational process under the condition of introduction of the pedagogical system into the process of training undergraduates in the specialty 073 «Management» have been outlined.